Sustainable Cultural Development: The Future Of Balinesse Adat Village Posterior The Enactment Of Law Number 6 Year 2014 Concerning Village - Nurjaya, I Nyoman (JATISWARA, 2018)
This study aims to find out the sustainable cultural development: the future of balinese adat village posterior the enactment of law number 6 year 2014 concerning village . This research is done empirically juridically, that is by collecting data by researching and examining legal implications posterior the enactment of Law Number 6 of 2014 regarding Village. In the sense of Explanation Article 6 Act Number 6 Year 2014 that stating: “This provision is intended to prevent the intersection in regions in term of authority, institutional duplication between Desa and Desa Adat within the same region, In contradiction, in case the Balinese and the Bali regional government as well is intended to chose the desa adat/desa pakraman to be registered with the hope to the only receive a village financial empowerment every year from the Government, should personally advice that there will be a number of legal consequences with the fate and future of existence and the life of desa adat/desa pakraman as a social and cultural system of Balinese Hindu community in particular and the whole traditional adat communities in the multicultural country of Indonesia in general.